2017
DOI: 10.1002/ajmg.b.32530
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of HIV‐associated neurocognitive disorder (HAND): A CHARTER group study

Abstract: HIV-associated neurocognitive disorder (HAND) often complicates HIV infection despite combination antiretroviral therapy (ART) and may be influenced by host genomics. We performed a genome-wide association study (GWAS) of HAND in 1,050 CNS HIV Anti-Retroviral Therapy Effects Research (CHARTER) Study participants. All participants underwent standardized, comprehensive neurocognitive and neuromedical assessments to determine if they had cognitive impairment as assessed by the Global Deficit Score (GDS), and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…HO-1 promoter (GT) n allele repeat lengths and the A(-413)T SNP genotype have modal distributions that suggest higher-risk genotypes in African Americans compared with European Americans To define relationships between HIV NCI, immune activation, and HO-1 (GT) n allele length in PLWH, we studied individuals (n = 606) in the CHARTER Genetics Cohort (table 1). 19,29 Of the 606 DNA samples, 3 were of insufficient quality to obtain reliable sequence data; therefore, HO-1 (GT) n allele data from 603 individuals were presented (table 1 and figure 1A). The distribution of HO-1 (GT) n allele lengths was trimodal (peaks at 23, 30, and 39), with a range of 13-44, and we assigned HO-1 (GT) n alleles as short "S" (<27), medium "M" (27-34), or long "L" (>34) (GT) n repeats (figure 1, A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HO-1 promoter (GT) n allele repeat lengths and the A(-413)T SNP genotype have modal distributions that suggest higher-risk genotypes in African Americans compared with European Americans To define relationships between HIV NCI, immune activation, and HO-1 (GT) n allele length in PLWH, we studied individuals (n = 606) in the CHARTER Genetics Cohort (table 1). 19,29 Of the 606 DNA samples, 3 were of insufficient quality to obtain reliable sequence data; therefore, HO-1 (GT) n allele data from 603 individuals were presented (table 1 and figure 1A). The distribution of HO-1 (GT) n allele lengths was trimodal (peaks at 23, 30, and 39), with a range of 13-44, and we assigned HO-1 (GT) n alleles as short "S" (<27), medium "M" (27-34), or long "L" (>34) (GT) n repeats (figure 1, A and B).…”
Section: Resultsmentioning
confidence: 99%
“…For analysis of HO-1 (GT) n allele genotypes, neurocognitive diagnosis, and plasma biomarkers, 606 PLWH were selected from the CHARTER Genetics Cohort, 19 based on reported availability of neurocognitive diagnosis data and DNA samples, and without other inclusionary or exclusionary criteria, to avoid potential bias. Of the 606 DNA samples, 3 were of insufficient quality to obtain reliable (GT) n sequence data; therefore, HO-1 (GT) n allele data from 603 individuals were presented (table 1 and figure 1A).…”
Section: Cohortsmentioning
confidence: 99%
“…With PARK2, there is a posited role of dopaminergic systems in PTSD and epidemiological evidence for association of Parkinson Disease and PTSD. [34][35][36] PODXL is involved in neural development and synapse formation, 37,38 SH3RF3 is associated with neurocognition and dementia, 39,40 and ZDHHC14 is associated with regulation of β -adrenergic receptors. 41,42 Finally, the HLA-B complex may be related through the known role of immunity and inflammation in stress-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Since many of these factors are controlled by the genetic make-up of the host, there is ongoing research into which genes may be associated with development and/or progression of HAND. Thus far, two genome-wide association studies (GWAS) have been conducted [ 55 , 56 ] and several candidate gene studies have investigated genes implicated in HAND and/or NCIs in HIV infected individuals (for an older, but thorough review, see Kellianpur and Levine (2014) and Levine, Parvos and Horvath (2014) [ 57 , 58 ]). Neither GWAS found any genes associated with HAD or milder neurocognitive impairments, as assessed by neuropsychological tests or global deficit score (GDS), that reached the genome-wide significance threshold.…”
Section: Risk Factors For Handmentioning
confidence: 99%
“…Neither GWAS found any genes associated with HAD or milder neurocognitive impairments, as assessed by neuropsychological tests or global deficit score (GDS), that reached the genome-wide significance threshold. However, the latter GWAS by Jia et al (2017), looking at GDS, found some biologically plausible gene variants previously associated with Alzheimer’s disease ( SH3RF3 and CSMD1 ), as well as four single nucleotide polymorphisms (SNPs) at the T-cell receptor alpha locus, involved in neurogenesis, which did approach significance [ 55 ]. Both studies were, however, limited by sample size, indicating a need for further research to support and validate previous findings.…”
Section: Risk Factors For Handmentioning
confidence: 99%